Peran Stakeholder dalam Pengembangan Kurikulum Berbasis Inovasi di SMP II Luqman Al Hakim 02 Batam - Nurhayati Nurhayati (Lembaga Pengembangan Kinerja Dosen, 2025)
Innovative education requires the development of a curriculum that is responsive to the demands of the times and the needs of students. At SMPII Luqman Al Hakim 02 Batam, the development of an innovation-based curriculum involves various stakeholders, including teachers, school principals, parents, the government, and the community. This study aims to identify the roles and contributions of each stakeholder in the process of developing an innovation-based curriculum at the school. Using a qualitative approach with a case study design, data were collected through in-depth interviews, focus group discussions (FGD), observations, and document analysis. The research findings show that teachers play a role as curriculum developers, the school principal serves as the director and facilitator, parents act as partners in the implementation, the government provides policies and funding, and the community represents the end users of the graduates. However, the main challenges faced include resource limitations and differing understandings of curriculum innovation among stakeholders. The implications of these findings highlight the importance of closer collaboration among stakeholders, enhancing their capacity to support the innovation-based curriculum, and the need for more comprehensive and targeted policies from the government to support the effective development of curricula in the future. This research provides valuable insights for educational policymakers in designing innovative and relevant curricula.